The Tour Guides Support Application Designed for Tour Participants - Damian PANASIUKand Zbigniew GLABINSKI (Communications of International Proceedings, 2024)
The tourism market has seen a steady increase in the number of travelers. A significant part of tourist travels are group trips organized by tour operator. The person responsible for implementing the trip on behalf of the tour operator is the tour leader. The article presents the use of a new original application that allows efficient management of a tourist group by a tour guide using a cell phone. It enables real-time communication at a distance between the tour guide and the participants, helps determine the location of the tourists and the tour leader by means of GPS, and allows to keep participants informed of changes during the program of the event.
Keywords: Management Of Tourist Group · Quality Of Tourism Services · Application Of New Technology To Tourism Industry.